Conventional Therapies Deplete Brain-Infiltrating Adaptive Immune Cells in a Mouse Model of Group 3 Medulloblastoma Implicating Myeloid Cells as Favorable Immunotherapy Targets - Abbas, Zahra; George, Courtney; Ancliffe, Mathew; Howlett, Meegan; Jones, Anya C.; Kuchibhotla, Mani; Wechsler-Reya, Robert J.; Gottardo, Nicholas G.; Endersby, Raelene (Frontiers in Immunology, 2022)
Medulloblastoma is the most common childhood brain cancer. Mainstay treatments of radiation and chemotherapy have not changed in decades and new treatment approaches are crucial for the improvement of clinical outcomes. To date, immunotherapies for medulloblastoma have been unsuccessful, and studies investigating the immune microenvironment of the disease and the impact of current therapies are limited. Preclinical models that recapitulate both the disease and immune environment are essential for understanding immune-tumor interactions and to aid the identification of new and effective immunotherapies. Using an immune-competent mouse model of aggressive Myc-driven medulloblastoma, we characterized the brain immune microenvironment and changes induced in response to craniospinal irradiation, or the medulloblastoma chemotherapies cyclophosphamide or gemcitabine. The role of adaptive immunity in disease progression and treatment response was delineated by comparing survival outcomes in wildtype C57Bl/6J and in mice deficient in Rag1 that lack mature T and B cells. We found medulloblastomas in wildtype and Rag1-deficient mice grew equally fast, and that craniospinal irradiation and chemotherapies extended survival equally in wildtype and Rag1-deficient mice, suggesting that tumor growth and treatment response is independent of T and B cells. Medulloblastomas were myeloid dominant, and in wildtype mice, craniospinal irradiation and cyclophosphamide depleted T and B cells in the brain. Gemcitabine treatment was found to minimally alter the immune populations in the brain, resulting only in a depletion of neutrophils. Intratumorally, we observed an abundance of Iba1+ macrophages, and we show that CD45high cells comprise the majority of immune cells within these medulloblastomas but found that existing markers are insufficient to clearly delineate resident microglia from infiltrating macrophages. Ultimately, brain resident and peripheral macrophages dominate the brain and tumor microenvironment and are not depleted by standard-of-care medulloblastoma therapies. These populations therefore present a favorable target for immunotherapy in combination with front-line treatments.